The Application of Balanced Scorecard for Private Hospitals in Shanghai - Mathew Valayil, Jacob (2012)
Purpose: The intent of the paper is to identify the main objectives and measures that will contribute to build a model of performance measurement system using balanced scorecard (BSC) for private (for-profit) hospitals in Shanghai. Design/methodology/approach: The design and methodology of this paper is based on an extensive literature review on the applications of balanced scorecard in various healthcare organizations. The primary research was carried out in three private hospitals in Shanghai. The research and data collection was done by interviews/discussions/surveys with the Senior Executives, doctors & staff of these hospitals and the residents of Shanghai. Based on the findings an adaptation of Balanced score card is suggested for the private hospitals in Shanghai. Findings: The literature review reveals that balanced scorecard was found effective for performance improvement in healthcare sector. The secondary research and the primary research conducted in Chinese private hospitals explore various performance objectives and measures used by these hospitals. The outcome of the research identifies the need for adopting a Balanced scorecard system in the private hospitals of Shanghai and reveals the need for aligning the vision of the hospitals to their operational strategies. Originality/value: The contribution of this paper is in identifying the key objectives and measures to implement the balanced scorecard for private (For-profit) hospitals in Shanghai.